ANALISIS STRATEGI KOMUNIKASI PEMASARAN DIGITAL DALAM MEMPROMOSIKAN BRAND “THE LIGHT OF ACEH” DI INSTAGRAM @ACEHTOURSIMTRAVEL - Muhammad Reza Maulana; Novi Susilawati (Jurnal Komunikasi & Media Digital, 2025)
The digital marketing communication strategy implemented by the Aceh Tourism Travel Team played an important role in promoting the brand “The Light of Aceh” on the @acehtourismtravel Instagram account. This research adopted the social media marketing concept by Gunelius. The purpose of this study was to explore the digital marketing strategy used to promote the brand “The Light of Aceh” on the @acehtourismtravel Instagram account. This research is a qualitative descriptive study, utilizing semi-structured interviews with two informants, observations on the Instagram account, and documentation of observation results. The research revealed the application of Gunelius's social media marketing concept in promoting the brand “The Light of Aceh.” The content creation strategies involved a partnership between the Aceh Culture and Tourism Office and experts within the Aceh Tourism Travel Team to create content, analyze Instagram algorithms, publish Islamic-themed content every Friday, and include the brand logo in the final content. Content sharing strategies involved adjusting distribution timing, using hashtags in the caption of the content, utilizing the Instagram Advertising feature, leveraging other social media platforms, and collaborating with public figures. Connecting strategies involved optimizing features such as Instagram collaboration posts, Instagram direct messages, and Instagram story reposts. Community-building strategies involved maintaining relationships with existing communities through the participation of Aceh Tourism Travel Team members in community activities, engaging the local community in content creation, and using call-to-action sentences in captions to engage the audience of the @acehtourismtravel Instagram account.